Uji Pertumbuhan Miselium Beberapa Nomor Isolat Jamur Merang (Volvariella volvaceae) FAPERTA UNSIKA pada G2 PDA dan G3 Baglog Secara In Vitro - Sari, Indah Permata; Lestari, Ani; Samaullah, Mohammad Yamin (JURNAL AGROPLASMA, 2023)
Straw mushroom is one of the horticultural commodities which in its development is still relatively new. Straw mushroom is one of the agricultural commodities that has a good future opportunity to be developed. The cultivation of straw mushrooms in Karawang has obstacles in obtaining superior seeds. Superior seedlings of straw mushrooms are seedlings that have mycelium that expands quickly and strongly and are free from bacterial contamination. This research was conducted at the Plant Breeding and Biotechnology Laboratory of Singaperbangsa University of Karawang, located on Jalan. HS Ronggowaluyo Telukjambe Timur, Karawang from December 2022 to February 2023. This study aims to obtain the best isolate number of straw mushroom (Volvariella volvaceae) Faperta Unsika on mycelium growth. The research method used was a single factor completely randomized design (CRD) consisting of 7 treatments A (FP White Elders), B (FP Semi Elders), C (FP022), D (FP028), E (FP029), F (FP030), G (FP031) and repeated 5 times. The effect on the treatment was analyzed by analysis of variance and if the F test at the 5% level was significant, then DMRT (Duncan Multiple Range Test) was conducted. The results showed that there was a significant effect of some isolates of straw mushroom (Volvariella volvaceae) Faperta Unsika on G2 PDA and G3 Baglog in Vitro on mycelium growth. Treatment D (FP028) gave the highest diameter result on mycelium growth on G2 PDA of 6.41 cm and the highest mycelium growth rate on G2 PDA of 1.76 cm/day. Treatment F (FP030) gave the highest length of mycelium growth of G3 baglog of 12.31 cm and the highest rate of mycelium growth of G3 baglog of 0.96 cm/day.Â Keywords: Straw mushroom, Faperta Unsika isolate, Mycelium